Microbiological findings in febrile neutropenic patients in a tertiary hospital of Southern Brazil - Zuckermann, Joice; Stoll, Paula; Meneghel, Rosane Lieberknecht; Kuchenbecker, Ricardo Souza; Santos, Rodrigo Pires; Moreira, Leila Beltrami (Clinical and Biomedical Research, 2012)
Background: Neutropenia is a major risk factor for infection. The prevalence of Gram-negative bacteria decreased in the early nineties, while the frequency of Gram-positive bacteria increased from between 55 to 70% of all bacteremia episodes. Even more recently there has been a resurgence of Gram-negative infections. The aim of this report is to describe the microbiological findings in a cohort of febrile neutropenic patients in a tertiary teaching hospital of Southern Brazil. Methods: This was a cohort study designed to evaluate the implementation of a clinical protocol for treatment of febrile neutropenic patients. Prospectively included in our study were patients with febrile neutropenia (FN) admitted between January 2004 and December 2005 at the Hospital de Clínicas of Porto Alegre. Historical controls were selected from patient visits recorded between March 2001 and April 2003 ‒ or recorded before the clinical protocol was introduced. Results: During the 2004-2005 and 2001-2003 study periods, 164 and 159 pathogens were documented, respectively. In 93 of 190 episodes (48.9%), and 84 of 193 episodes (43.5%) there were documented microbiological infections. Fungal infection was documented in very few episodes (6.1 vs. 5.7%). We also observed a 52.8% prevalence of Gram-positive and a 47.2% prevalence of Gram-negative bacteria in the 2001‒2003 period. Observed in the 2004‒2005 period were 38.1% Gram-positive and 61.9% Gram-negative bacteria (P=0.012). There was also a significant increase in Pseudomonas aeruginosa prevalence in the second study period (1.9 to 11.6%; P<0.001). Six isolates (31.6%) were discovered to be multi-resistant in the 2004‒2005 period versus none in the first period. The prevalence of Oxacillin-resistant Staphylococcus was 53.5 and 65.8% in the first and second periods, respectively (P=0.23). Conclusion: These documented pathogens are the most commonly observed in febrile neutropenic patients, but the emergence of multidrug-resistant Pseudomonas aeruginosa is of some concern.